Experiences of peak performance in elite american football - Gillham, A.; Stone, C. (The Sport Psychologist, 2020)
Elite athletes strive for a superior state of psychological functioning to achieve peak performance, and peak performance is the central construct of this study. Peak performance as a phenomenon is a state of superior functioning allowing athletes to perform at their highest levels, attaining outstanding results. The purpose of this study was to understand the phenomenon of peak performance through semistructured interviews with 16 elite-level American football players. Four higher-order themes divided into mental, physical, emotional, and sensory elements. Those themes are supported by 18 lower-level categories. Findings were largely consistent with previous research despite this being the first study to include American football players. A specific noteworthy conclusion is the connection between mental and physical components that provides ample opportunities for both researchers and applied practitioners. In addition, the participant quotes prompted a return to the discussion of the connection between individual zones of optimal functioning, peak performance, and flow states.